Membrane trafficking directed by VAMP2 and syntaxin 3 in uterine epithelial cells. Issue 4 (October 2020) - Kalam, Sadaf N; Cole, Louise; Lindsay, Laura; Murphy, Christopher R
Abstract : Luminal uterine epithelial cells (UEC) have a surge in vesicular activity during early uterine receptivity. It has been predicted these vesicles exit the UEC via exocytosis resulting in secretion and membrane trafficking. The present study investigated the changes in SNARE proteins VAMP2 (v-SNARE) and syntaxin 3 (t-SNARE) localisation and abundance in UECs during early pregnancy in the rat. We found VAMP2 and syntaxin 3 are significantly higher on day 5.5 compared to day 1 of pregnancy. On day 5.5, VAMP2 is perinuclear and syntaxin 3 is concentrated in the apical cytoplasm compared to a cytoplasmic localisation on day 1. This change in localisation and abundance show VAMP2 and syntaxin 3 are involved in vesicular movement and membrane trafficking in UECs during early pregnancy. This study also investigated the influence of cytoskeletal disruption of microtubules and actin filaments on VAMP2 and syntaxin 3 in UECs grown in vitro, since microtubules and actin influence vesicle trafficking. As expected, this study found disruption to microtubules with colchicine and actin with cytochalasin D impacted VAMP2 and syntaxin 3 localisation. These results suggest VAMP2 and syntaxin 3 are involved in the timely trafficking of vesicular membranes to the apical surface in UECs during early pregnancy, as are of microtubules and actin.